Frontiers of surface-enhanced raman scattering : single-nanoparticles and single cells - Ozaki, Y. (Yukihiro); Kneipp, Katrin; Aroca, Ricardo (Chichester, West Sussex, UK : Wiley, 2014)
A comprehensive presentation of Surface-Enhanced Raman Scattering (SERS) theory, substrate fabrication, applications of SERS to biosystems, chemical analysis, sensing and fundamental innovation through experimentation. Written by internationally recognized editors and contributors. Relevant to all those within the scientific community dealing with Raman Spectroscopy, i.e. physicists, chemists, biologists, material scientists, physicians and biomedical scientists. SERS applications are widely expanding and the technology is now used in the field of nanotechnologies, applications to biosystems, nonosensors, nanoimaging and nanoscience.
4.2.2 Intensity and Spectral Fluctuation in SERS and SEF4.2.3 Framework for Analysis of Fluctuation in SERS and SEF; 4.2.4 Analysis of Intensity Fluctuation in SERS and SEF; 4.2.5 Analysis of Spectral Fluctuation in SERS and SEF; 4.2.6 Summary; 4.3 Conclusion; Acknowledgments; References; Chapter 5 Single-Molecule Surface-Enhanced Raman Scattering as a Probe for Adsorption Dynamics on Metal Surfaces; 5.1 Introduction; 5.2 Simultaneous Measurements of Conductance and SERS of a Single-Molecule Junction; 5.3 SERS Observation Using Heterometallic Nanodimers at the Single-Molecule Level.
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Raman effect, Surface enhanced; Surfaces (Physics); Raman spectroscopy; Spectrum analysis; Raman effect, Surface enhanced; Raman spectroscopy; Spectrum analysis; Surfaces (Physics); Electronic books; Electronic books